Pulling Strings with Puppet Configuration Management Made Easy - Turnbull, James; SpringerLink (Online service) (Berkeley, CA : Apress, 2007)
Competent system administrators know their success hinges upon being able to perform often tedious tasks with rigor and punctuality. Such metrics are often achieved only by instituting a considerable degree of automation, something that has become even more crucial as IT environments continue to scale both in terms of size and complexity. One of the most powerful system administration tools to be released is Puppet, a solution capable of automating nearly every aspect of a system administrator's job, from user management, to software installation, to even configuring server services such as FTP and LDAP. Pulling Strings with Puppet: Configuration Management Made Easy is the first book to introduce the powerful Puppet system administration tool. Author James Turnbull will guide you through Puppet's key features, showing you how to install and configure the software, create automated Puppet tasks, known as recipes, and even create reporting solutions and extend Puppet further to your own needs. A bonus chapter is included covering the Facter library, which makes it a breeze to automate the retrieval of server configuration details such as IP and MAC addresses.
Introducing Puppet -- Installing and Running Puppet -- Speaking Puppet -- Using Puppet -- Reporting on Puppet -- Advanced Puppet -- Extending Puppet.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books